Night of the ninth dragon - Osborne, Mary Pope; Murdocca, Sal (New York : Random House, 2018)
Introduces readers to classic Welsh legends as Jack and Annie return to Camelot to assist King Arthur, Merlin, and the Knights of the Round Table.
"A Stepping Stone book."
Keywords: Arthur, -- King -- Fiction; Arthur, -- King -- Fiction; Time travel -- Fiction; Merlin (Legendary character) -- Fiction; Magic -- Fiction; Brothers and sisters -- Fiction; Camelot (Legendary place) -- Fiction; Dragons -- Fiction; Adventures and adventurers -- Fiction; Time travel -- Fiction; Merlin (Legendary character) -- Fiction; Magic -- Fiction; Brothers and sisters -- Fiction; Camelot (Legendary place) -- Fiction; Dragons -- Fiction; Adventures and adventurers -- Fiction